DEP domain‐containing mTOR‐interacting protein in the rat brain: Distribution of expression and potential implication. Issue 1 (22nd September 2014) - Caron, Alexandre; Baraboi, Elena‐Dana; Laplante, Mathieu; Richard, Denis
ABSTRACT DEP domain–containing mTOR‐interacting protein (DEPTOR) has been recently discovered as an endogenous regulator of the mechanistic target of rapamycin complex 1 (mTORC1) and mTORC2. mTORC1 is present in the brain, and there is growing evidence that its dysregulation contributes to several brain alterations. This suggests the involvement of mTOR signaling and its modulators in neurobiological controls. Here, we characterized and mapped the expression of DEPTOR in the rat brain. We show that DEPTOR was widely expressed from the forebrain to the hindbrain, including the hippocampus, the mediobasal hypothalamus, and the circumventricular organs (CVOs). In the hippocampus, DEPTOR protein and Deptor mRNA were highly expressed in the dendate gyrus and CA3 field. In the CVOs, DEPTOR was expressed in the subfornical organ, the median eminence, and the area postrema. In the mediobasal hypothalamus, DEPTOR was expressed in neurons of the ventromedial nucleus (VMH) and colocalized with proopiomelanocortin (POMC) in the arcuate nucleus (ARC). The hypothalamic distribution suggested a role for DEPTOR in energy balance. Supporting this possibility, we observed that Deptor hypothalamic expression was modulated by the nutritional status in a context of diet‐induced and genetic obesity; food deprivation increased Deptor mRNA in both the ARC and VMH of obese rats. In conclusion, the present results illustrate the presence of DEPTOR in the rat brain and suggest a role for DEPTOR in the hypothalamic regulation of energy balance, which further supports the role of mTOR in energy homeostasis. J. Comp. Neurol. 523:93–107, 2015. © 2014 Wiley Periodicals, Inc.